2000
DOI: 10.1097/00004347-200010000-00015
|View full text |Cite
|
Sign up to set email alerts
|

Epithelioid Trophoblastic Tumor Metastatic to the Vagina: An Immunohistochemical and Ultrastructural Study

Abstract: We describe an epithelioid trophoblastic tumor (ETT) metastatic to the vagina in a 30-year-old Japanese woman. A polypoid tumor in the vaginal orifice was composed of nests of intermediate trophoblastic cells that showed a striking epithelioid appearance. In the hysterectomy specimen, a tumor infiltrated through the myometrium and showed histologic findings similar to those of the vaginal tumor. The tumor cells were positive for cytokeratin, inhibin-alpha, and melanoma cell adhesion molecule (Mel-CAM, CD146) b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
23
1

Year Published

2002
2002
2021
2021

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 45 publications
(26 citation statements)
references
References 10 publications
1
23
1
Order By: Relevance
“…In ETT, immunohistochemical stains for b-hCG, hPL exhibit focal reactivity. This is in distinct contrast to the staining patterns seen in choriocarcinoma and PSTT [7]. In choriocarcinoma, b-hCG is diffusely positive [14], whereas hPL positive cells are less conspicuous.…”
Section: Discussioncontrasting
confidence: 71%
See 2 more Smart Citations
“…In ETT, immunohistochemical stains for b-hCG, hPL exhibit focal reactivity. This is in distinct contrast to the staining patterns seen in choriocarcinoma and PSTT [7]. In choriocarcinoma, b-hCG is diffusely positive [14], whereas hPL positive cells are less conspicuous.…”
Section: Discussioncontrasting
confidence: 71%
“…All previously reported extrauterine ETT included lung, vagina, broad ligament, fallopian tube, gallbladder, paracervix and parametrium, probably originating from uterine trophoblastic disease [6][7][8][9][10][11][12]. Pancreas metastasis in our study, to our knowledge, was the first case reported.…”
Section: Discussionsupporting
confidence: 49%
See 1 more Smart Citation
“…Positivity for hCG is usually focal and primarily seen in syncytiotrophoblasts [4,22,24]. Focal positivity can also be seen for human placental lactogen [26]. …”
Section: Discussionmentioning
confidence: 99%
“…However, the Ki-67 labeling index can range from 2 to 86% with an average of 30% [2,24]. ETT is negative for CK5/6, CD68, S100, desmin, vimentin, TTF1, cytokeratin 20, estrogen receptor, progesterone receptor and p53 [12,22,26]. The hyaline material has been shown to be positive for type IV collagen and fibronectin of oncofetal and adult types [4].…”
Section: Discussionmentioning
confidence: 99%